Inguinal Hernia Containing Uterus, Fallopian Tube, and Ovary in a Premature Newborn - Kıvılcım Karadeniz Cerit; Rabia Ergelen; Emel Colak; Tolga E. Dagli (Case Reports in Pediatrics)
A female infant weighing 2,200 g was delivered at 34 weeks of gestation by vaginal delivery. She presented with an irreducible mass in the left inguinal region at 32 days of age. An ultrasonography (US) was performed and an incarcerated hernia containing uterus, fallopian tube, and ovary was diagnosed preoperatively. Surgery was performed through an inguinal approach; the uterus, fallopian tube, and ovary were found in the hernia sac. High ligation and an additional repair of the internal inguinal ring were performed. Patent processus vaginalis was found during contralateral exploration and also closed. The postoperative course was uneventful. After one year of follow-up, there have been no signs of recurrence.